Implications of Nominee Agreements in Land Ownership by Foreign Nationals in Bali: Case Study of Nominee Agreement in Decision No. 274/Pdt.G/2020/PN Dps - Ridhogusti, Rinaldi; Kurniati, Grasia (Reformasi Hukum, 2024)
The nominee agreement is often used to circumvent the prohibition on land ownership by Foreign Nationals (WNA), where the land is officially registered under the name of an Indonesian Citizen (WNI) but controlled by a WNA. This practice raises legal and social issues, particularly in Bali. This study aims to analyze the legal and social implications of the nominee agreement in land ownership by WNA, with a focus on Decision No. 274/Pdt.G/2020/PN Dps. This study uses a normative juridical method, with a case approach and legal literature analysis to examine the legality and impacts of the nominee agreement practice. The study finds that the nominee agreement violates the Basic Agrarian Law No. 5 of 1960 and Article 1320 of the Civil Code regarding the requirements for valid agreements. The court's ruling to annul all nominee agreements demonstrates a commitment to enforcing agrarian law and preventing illegal practices. Stricter law enforcement, strengthened regulations, enhanced supervision, and comprehensive legal education are needed to address nominee agreements and ensure that land ownership is managed fairly and sustainably by Indonesian citizens (WNI).